Age over sex: evaluating gut microbiota differences in healthy Chinese populations - Wu, Jiacheng; Shen, Hexiao; Lv, Yongling; He, Jing; Xie, Xiaotian; Xu, Zhiyue; Yang, Pengcheng; Qian, Wei; Bai, Tao; Hou, Xiaohua (Frontiers in Microbiology, 2024)
Age and gender have been recognized as two pivotal covariates affecting the composition of the gut microbiota. However, their mediated variations in microbiota seem to be inconsistent across different countries and races. Here, 613 individuals whom we referred to as the "healthy" population were selected from 1018 volunteers through rigorous criteria for 16S rRNA sequencing.Three enterotypes were identified, including Escherichia-Shigella, mixture (Bacteroides and Faecalibacterium), and Prevotella. Moreover, eleven covariates that explain the differences in microbiota were determined, with age being the predominant factor. Next, age-related differences in alpha diversity, beta diversity, and core genera were observed in our cohort. Remarkably, after adjusting for ten covariates other than age, a sea of genera that differed between age groups were demonstrated. In contrast, minimal differences in alpha diversity, beta diversity, and differential abundant genera were observed between males and females. Furthermore, we also demonstrated the age trajectories of several well-known beneficial genera, LPS-producing genera, and SCFAsproducing genera. Overall, our study further elucidated the effects mediated by age and gender on microbiota differences, which are of significant importance for a comprehensive understanding of the gut microbiome spectrum in healthy individuals.